1984
DOI: 10.1073/pnas.81.14.4270
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for alanine in the amino acid control of deprivation-induced protein degradation in liver.

Abstract: Protein degradation in liver is actively controlled by a small group of inhibitory amino acids-leucine, tyrosine (or phenylalanine), glutamine, proline, histidine, tryptophan, and methionine. Other evidence, however, suggests that one or more of the remaining 12 noninhibitory amino acids is also required for suppression of proteolysis at normal concentrations. This question was investigated in livers of fed rats perfused in the single-pass mode. The deletion of alanine at normal (lx), but not at 4x or 1Ox norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 32 publications
0
6
0
4
Order By: Relevance
“…The effect of specific amino acids has been extensively studied in the past and a group of specific single amino acids was shown to inhibit autophagy-mediated proteolysis. [20][21][22][23][24] To test whether induction of autophagy by specific amino acids is detectable by FACS analysis, cells stably expressing GFP-LC3 were incubated for 5 hours in medium, systematically omitted of a specific single amino acid and the level of autophagic activity was examined using flow cytometry. As shown in Figure 4A, only specific amino acids inhibit autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of specific amino acids has been extensively studied in the past and a group of specific single amino acids was shown to inhibit autophagy-mediated proteolysis. [20][21][22][23][24] To test whether induction of autophagy by specific amino acids is detectable by FACS analysis, cells stably expressing GFP-LC3 were incubated for 5 hours in medium, systematically omitted of a specific single amino acid and the level of autophagic activity was examined using flow cytometry. As shown in Figure 4A, only specific amino acids inhibit autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…John, 1976;Poso and Mortimore, 1984), a number of studies have now shown that other nonlysosomal proteases are also involved in metabolic turnover of intracellular proteins (Zeman et al, 1985;Hough et al, 1986;Fagan et al, 1987). The lack of definitive information on the proteases involved and the inability thus far to analyze intracellular protein degradation by monitoring intermediates in the degradation process have hampered studies on the mechanism of intracellular protein degradation.…”
mentioning
confidence: 96%
“…The observations on RNA degradation presented in Figure 1 showed a gradual and continuous inhibitory effectiveness of the eight amino acids known as regulators of proteolysis. In perfused livers, the inhibitory effectiveness of this regulatory group on protein degradation nearly disappeared within a narrow zone between 0.5 and four times normal plasma concentration of amino acids (Poso and Mortimore, 1984;. Such a loss of inhibition did not appear for the degradation of RNA in cultured rat hepatocytes with physiological concentration of regulatory amino acids (AA8 group).…”
Section: Discussionmentioning
confidence: 96%